2011
DOI: 10.1016/j.jesp.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Do observer ratings validate self-reports of intergroup contact?: A round-robin analysis

Abstract: Two studies used a round-robin design to examine whether the observers made consensual judgments of targets' degree and quality of intergroup contact, and whether these consensual judgments were correlated with the targets' own self ratings, and moderated by the observability of the contact. Study 1 revealed projection/assumed similarity, with participants rating others as similar to themselves to a large extent, but also yielded evidence for the validity of whites' self-reports of direct, but not extended, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 56 publications
2
40
0
Order By: Relevance
“…Their research included two items measuring cross-group friendships that were almost identical to those used in Turner et al (2007a, Study 3), as well as contact quantity and quality items based on those found in Islam and Hewstone (1993). Therefore, the Hewstone et al (2011) study lends crucial support to the convergent validity of such self-report measures of intergroup contact using the items we have highlighted here (see also Dhont, Van Hiel, De Bolle, & Roets, 2012, for additional evidence). …”
Section: Results and Commentsmentioning
confidence: 54%
See 1 more Smart Citation
“…Their research included two items measuring cross-group friendships that were almost identical to those used in Turner et al (2007a, Study 3), as well as contact quantity and quality items based on those found in Islam and Hewstone (1993). Therefore, the Hewstone et al (2011) study lends crucial support to the convergent validity of such self-report measures of intergroup contact using the items we have highlighted here (see also Dhont, Van Hiel, De Bolle, & Roets, 2012, for additional evidence). …”
Section: Results and Commentsmentioning
confidence: 54%
“…However, Hewstone, Judd, and Sharp (2011) demonstrated that respondents' ratings of their own intergroup contact were highly correlated with observer ratings. Their research included two items measuring cross-group friendships that were almost identical to those used in Turner et al (2007a, Study 3), as well as contact quantity and quality items based on those found in Islam and Hewstone (1993).…”
Section: Results and Commentsmentioning
confidence: 97%
“…However, recent research by Hewstone, Sharp, and Judd (2009) found evidence that observers' reports (e.g. participants' friends and family members) and self-reports of contact were significantly associated, which constitutes a validation of self-report measures of contact.…”
Section: Discussionmentioning
confidence: 86%
“…'; pre = .79; post = .91). Students further expressed attitudes towards the out-group on a feeling thermometer (see e.g., Hewstone, Judd, & Sharp, 2011; 0°C = least warm; 100°C = most warm) as well as positive attitude forecasting (before the CMIC) and positive explicit outgroup attitudes (after the CMIC) on a three-item scale ('I think I (will) really like students from the University B', 'I think students from the University B are really friendly. ', 'I would not trust students from the University B' (reversed); pre = .85; post = .68).…”
Section: Methodsmentioning
confidence: 99%